Legal Protection Against Default Of Apartment Sale And Purchase Agreement: (Case Study Of Pt Prospek) - Rafi Muhammad Irvan; Diani Sadiawati (UNIVERSITAS PAKUAN, 2026)
Bankruptcy and Suspension of Debt Payment Obligation (PKPU) proceedings involving property developers frequently generate significant legal uncertainty for apartment buyers who have fulfilled payment obligations but have not received the promised units. In practice, homologation decisions approving settlement plans often require consumers to continue payments despite prior breaches of contract, including construction delays or project abandonment. This situation creates tension between the binding nature of homologation under bankruptcy law and consumers’ contractual rights under civil and consumer protection law. An examination of the Indonesian Civil Code, Consumer Protection Law, and Bankruptcy and PKPU Law demonstrates that a developer’s breach of contract entitles buyers to claim specific performance, contract termination, or compensation. The principle of exceptio non adimpleti contractus legitimizes a buyer’s refusal to perform further obligations when the counterparty has failed to fulfill its own. Empirical findings reveal structural bargaining power imbalance and limited legal certainty for consumers positioned as concurrent creditors within insolvency proceedings. A developer’s liability does not extinguish upon bankruptcy but remains inherent in the obligation to restore losses in accordance with good faith and contractual justice. Harmonization between bankruptcy and consumer protection regimes is therefore essential to ensure substantive justice for property buyers.